Bildung als Perspektive für Care Leaver? Bildungschancen und Bildungswege junger Erwachsener mit Kinder- und Jugendhilfeerfahrung - Groinig, Maria (Schriftenreihe der ÖFEB-Sektion Sozialpädagogik, 2019)
In the book, the results of a study are presented, with the help of which systematic knowledge about the educational, training and professional situation of Care Leavern in Austria was obtained for the first time and in which the interaction of educational processes and social context conditions of growing up was examined with the help of quantitative and qualitative research approaches .